Pengaruh Tingkat Pendidikan, Modal Usaha, dan Teknologi Terhadap Pendapatan UMKM Pesisir di Nagari Katapiang - Yulianis, Fitri; Susanto, Perengki; Abror, Abror; Nofranita, Willy; Alfarisi, Salman; Akmal, Nurul Asmaa; Erniwati, Erniwati (Badan Penelitian and Pengembangan (Balitbang), Padang, West Sumatra, Indonesia, 2025)
Micro, Small, and Medium Enterprises (MSMEs) play a strategic role in local economic development due to their contribution to employment creation and income distribution, particularly in coastal areas. However, the development of MSMEs remains constrained by limited business capital, variations in entrepreneurs’ education levels, and suboptimal utilization of technology. This study aims to analyze the effect of education level, business capital, and technology utilization on the income of MSMEs in Katapiang Nagari, Batang Anai District, Padang Pariaman Regency. This research employed a quantitative approach using multiple linear regression analysis. The sample was selected through purposive sampling involving 50 micro-scale culinary MSME owners operating in the coastal area of Katapiang Beach. Data were collected through questionnaires and analyzed using SPSS version 22. The results show that business capital has a positive and significant effect on MSME income, while education level and technology utilization do not have a significant effect. The coefficient of determination (R²) of 0.45 indicates that 45% of income variation can be explained by the three independent variables. These findings suggest that MSME income improvement in Katapiang Nagari is more strongly influenced by capital adequacy. Therefore, it is recommended that local governments prioritize strengthening access to MSME financing schemes and integrated financial management assistance, accompanied by gradual and practical digital capacity development aligned with the characteristics of coastal culinary enterprises.